The ϕ-Topological Conformal Dimension for the Sierpinski Carpet. Issue 1 (2nd January 2022) - Mabrouk, Anouar Ben; Douzi, Zied; Selmi, Bilel
Abstract: In this paper, a generalized fractal dimension is introduced based on a combination of the topological dimension, conformal dimension, and the ϕ -conformal dimension. Lower and upper bound estimates of the new variant of dimension are provided for the case of the Sierpinski carpet fractal set. Moreover, the equality of such bounds is proved for a large class of the basic measure ϕ .